Pacing for Patients Suffering From Cardioinhibitory Vasovagal Syncope Using the Closed-Loop System - Barón-Esquivias, Gonzalo; Barón-Solís, Carmen; Ordóñez, Antonio (Frontiers in Cardiovascular Medicine, 2020)
One in three vasovagal syncope (VVS) patients has syncopal recurrence after diagnosis despite the standard recommendations for avoidance of recurrence, one in five has more than one syncopal recurrence in the medium term. Given the high prevalence of VVS, there is a large population that continues to need effective treatment. There are numerous studies that use the implantable loop recorder (ILR) to document a cardioinhibitory response during VVS with one study, ISSUE-3, demonstrating efficacy of pacing using the rate-drop response algorithm to trigger pacing and prevent syncopal recurrence in this population. There are more uncertainties in the studies that have used head-up tilt test (HUT) to select the population for pacing. We have recently performed the SPAIN randomised controlled clinical trial using HUT to select patients for pacing. The conclusion of the study was that with the Closed-Loop-System to introduce pacing there was significant reduction in the burden of syncope and a seven-fold increase in time to first recurrence of syncope which was greater than in the ISSUE-3 study. Since the completion of the SPAIN trial and its inclusion in European guidelines, in our daily clinical practice, the use of this therapy is still recommended with caution in the context of the available literature, but it has increased our confidence in so doing. Conclusions: One in five patients with VVS needs treatment because of a high syncopal load. If an ILR is used to select patients for pacing, the rate-drop-response algorithm can be recommended. In patients, who have asystole on HUT, pacing with the Closed-Loop-System has higher success and must now be considered a tenable option for VVS patients.